2020
DOI: 10.1111/jog.14619
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide study of mortality and survival in pregnancy‐related streptococcal toxic shock syndrome

Abstract: Aim Streptococcal toxic shock syndrome is associated with the highest infection‐related maternal mortality rates. We conducted a comparative analysis of the background factors and treatment course between survivors and nonsurvivors to improve our understanding concerning the optimal initial treatment approach for this fulminant disease. Methods This retrospective observational study was conducted based on clinical data collected from two national organizations. Clinical data of patients who died or survived (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Online supplemental file presents the risk of bias assessment of the 41 included studies. The majority of studies were rated as high risk of bias overall owing to residual confounding and lack of adjustment for confounding in statistical analyses (37/41, 90%) 2 5 6 10 35–67. Three studies were rated at moderate risk of bias overall7 14 68 and one at low risk of bias overall 11…”
Section: Resultsmentioning
confidence: 99%
“…Online supplemental file presents the risk of bias assessment of the 41 included studies. The majority of studies were rated as high risk of bias overall owing to residual confounding and lack of adjustment for confounding in statistical analyses (37/41, 90%) 2 5 6 10 35–67. Three studies were rated at moderate risk of bias overall7 14 68 and one at low risk of bias overall 11…”
Section: Resultsmentioning
confidence: 99%
“…A recent national survey in Japan showed that the number of patients in the group of survivors of perinatal STSS who had received intensive treatment within 1 h of onset of fulminant stage was larger than the number of patients in the mortality group [5]. Furthermore, the percentage of patients who received systematic antibiotic treatment at the first visit in that study was significantly higher in the survivor group than in the mortality group [5]. In our case, we experienced fulminant STSS in mid-pregnancy, and the patient was cured and survived without any complications after starting prompt systemic antibiotic treatment and intensive care.…”
Section: Introductionmentioning
confidence: 99%
“…The fulminant form of STSS by S. pyogenes is the most popular cause of infectious maternal death [4]. A recent national survey in Japan showed that the number of patients in the group of survivors of perinatal STSS who had received intensive treatment within 1 h of onset of fulminant stage was larger than the number of patients in the mortality group [5]. Furthermore, the percentage of patients who received systematic antibiotic treatment at the first visit in that study was significantly higher in the survivor group than in the mortality group [5].…”
Section: Introductionmentioning
confidence: 99%